2020
DOI: 10.1177/1179547620965560
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity After Surgical Menopause Treated with Individualized Classical Homeopathy: A Case Report

Abstract: Classical homeopathy was shown to be beneficial in climacteric syndrome in many studies, but the clinical effect is unclear. To inspect if individualized classical homeopathy has a role in treating complaints after surgical menopause through real world case, we present a case of a 54-year-old Russian woman treated with individualized classical homeopathy for multimorbid conditions after surgical menopause examined for changes from homeopathic treatment. We assessed changes in climacteric symptoms, changes in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Though observational studies have shown encouraging results in reducing the severity and frequency of hot flashes in women treated with homeopathy, few RCTs have shown positive results; some have small sample sizes, most of them do not use a homogeneous classification of women according to international standards (STRAW þ 10), 47 and the longest follow-up is two years (a case report by Mahesh and colleagues). 48 An open, multi-national, prospective, pragmatic and noncomparative observational study by Bordet et al 49 included 438 menopausal women and concluded that 50% of the patients who had had daily hot flashes at baseline no longer suffered them at the final homeopathy visit. The number of diurnal and nocturnal hot flashes fell significantly between baseline and follow-up visits (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Though observational studies have shown encouraging results in reducing the severity and frequency of hot flashes in women treated with homeopathy, few RCTs have shown positive results; some have small sample sizes, most of them do not use a homogeneous classification of women according to international standards (STRAW þ 10), 47 and the longest follow-up is two years (a case report by Mahesh and colleagues). 48 An open, multi-national, prospective, pragmatic and noncomparative observational study by Bordet et al 49 included 438 menopausal women and concluded that 50% of the patients who had had daily hot flashes at baseline no longer suffered them at the final homeopathy visit. The number of diurnal and nocturnal hot flashes fell significantly between baseline and follow-up visits (p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Though observational studies have shown encouraging results in reducing the severity and frequency of hot flashes in women treated with homeopathy, few RCTs have shown positive results; some have small sample sizes, most of them do not use a homogeneous classification of women according to international standards (STRAW + 10), 47 and the longest follow-up is two years (a case report by Mahesh and colleagues). 48…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations